Towards chronic deep brain stimulation in freely moving hemiparkinsonian rats: applicability and functionality of a fully implantable stimulation system. (16th March 2021) - Apetz, Nadine; Paralikar, Kunal; Neumaier, Bernd; Drzezga, Alexander; Wiedermann, Dirk; Iyer, Rajesh; Munns, Gordon; Scott, Erik; Timmermann, Lars; Endepols, Heike
Abstract : Objective. This study aimed at investigating a novel fully implantable deep brain stimulation (DBS) system and its ability to modulate brain metabolism and behavior through subthalamic nucleus (STN) stimulation in a hemiparkinsonian rat model. Approach. Twelve male rats were unilaterally lesioned with 6-hydroxydopamine in the medial forebrain bundle and received a fully implantable DBS system aiming at the ipsilesional STN. Each rat underwent three cylinder tests to analyze front paw use: a PRE test before any surgical intervention, an OFF test after surgery but before stimulation onset and an ON test under DBS. To visualize brain glucose metabolism in the awake animal, two [ 18 F]FDG scans were conducted in the OFF and ON condition. At least 4 weeks after surgery, an [ 18 F]FDOPA scan was used to check for dopaminergic integrity. Main results. In general, STN DBS increased [ 18 F]FDG uptake ipsilesionally and decreased it contralesionally. More specifically, bilateral orbitofrontal cortex, ipsilateral caudate putamen, sensorimotor cortex and nucleus accumbens showed significantly higher tracer uptake in ON compared to OFF condition. Contralateral cingulate and secondary motor cortex, caudate putamen, amygdala, hippocampus, retrosplenial granular cortex, superior colliculus, and parts of the cerebellum exhibited significantly higher [ 18 F]FDG uptake in the OFF condition. On the behavioral level, stimulation was able improve use of the contralesional affected front paw suggesting an effective stimulation produced by the implanted system. Significance. The fully implantable stimulation system developed by us and presented here offers the output of arbitrary user-defined waveforms, patterns and stimulation settings and allows tracer accumulation in freely moving animals. It is therefore a suitable device for implementing behavioral PET studies. It contributes immensely to the possibilities to characterize and unveil the effects and mechanisms of DBS offering valuable clues for future improvements of this therapy.